Sarcoidosis presenting with an acute Guillain-Barré syndrome. Issue 768 (October 1989) - Miller, R.; Sheron, N.; Semple, S.
Abstract : A 28 year old Caucasian male presented with an acute Guillain-Barré syndrome and bilateral facial weakness. He had an abnormal chest radiograph. Lumbar puncture revealed acellular fluid with a raised protein count and lung function tests showed a restrictive ventilatory defect. The patient deteriorated and required mechanical ventilation for 14 days. Steroids and plasmapheresis were not used and the patient spontaneously recovered. Two months after presentation limb power was almost normal but there was residual partial bilateral facial weakness. The chest radiograph remained abnormal and repeat lung function tests showed a persistent restrictive ventilatory defect and a reduced gas transfer coefficient. A transbronchial biopsy revealed non-caseating granulomata. The association between neurosarcoidosis and Guillain-Barré polyneuropathy is discussed and the literature reviewed.